Ascorbic Acid Based Ionic Liquids: Recyclable and Efficient Catalytic Systems for the Huisgen Cycloaddition - Koguchi, Shinichi; Nakamura, Kaori (Synlett, 2013)
A new method for the Huisgen cycloaddition using an ascorbic acid based ionic liquid and a copper catalyst in an ionic liquid, under microwave irradiation, is described. The reaction times are short and a simple procedure for separation of the products is established. Good conversions are obtained and the ionic liquid based catalytic system can be recycled.
Keywords: ionic liquids; microwave irradiation; supported catalysis; heterocycles; oxidation